(untitled) (Innovaciones Educativas, 2025)
Universities face an educational challenge that requires focused attention on the development of soft skills. These skills are an essential part of innovative learning, play a key role in the holistic formation of young people, and are highly valued by employers. The main objective of this study is to promote the development of soft skills among students in higher education. A mixed-methods approach was used, with a descriptive, non-experimental research design. The scientific methods employed allowed researchers to examine the subject closely, and the use of validated instruments yielded a Cronbach’s alpha value of 0.80. The study population consisted of 50 faculty members and 1,090 students, from which a stratified random sample of 88 students and of all faculty members was selected. The results identified aspects related to the level of teaching practice, pedagogical skills, and technological resources, as well as the main deficiencies observed in students. It is concluded that fostering soft skills among higher education students leads to meaningful learning and better preparation for professional life, as these competencies are essential for successful performance. Conversely, a lack of development in this area may result in difficulties across personal, social, academic, and professional domains. The article also presents a proposal that includes a set of formative activities designed to help students become more collaborative, adaptable, proactive, resilient, and responsible.